Left Atrial Enlargement an Early Predictor for Development of Systolic Dysfunction – Results of a Cross-Sectional Study Conducted in Georgia - Eka Rukhadze; Nino Tabagari-Bregvadze; Levan Tvildiani (European Scientific Journal, ESJ, 2017)
Background and Aims: Left ventricular systolic dysfunction, even asymptomatic, is associated with the development of heart failure (HF) and all-cause mortality. Left ventricular ejection fraction (LVEF) is the most commonly used marker of left ventricular systolic function. It is well established that early detection and treatment of reduced LVEF, as well as the aggressive management of predisposing conditions, delays the manifestation of HF. Our study aimed to measure the association between LVEF and other echocardiographic variables in a population with LVEF within the normal range and without symptoms of HF. Methods: We conducted a cross-sectional study in 2008-2009. Results: We analyzed echocardiographic and clinical data of 146 patients: 66.4% were women; mean age was 55 (40 –69 years). LVEF significantly correlated only with left atrium (LA) size (Beta -0.266, p < 0.05). The correlation was inverse and remained significant after adjusting for age, gender, obesity, diabetes, arterial hypertension, left ventricular hypertrophy, pulmonary systolic pressure, mitral regurgitation, and diastolic dysfunction. Conclusions: We found that the earliest structural change associated with LVEF tendency to decrease was LA size. Further research is needed to assess the LA enlargement as an early predictor of systolic dysfunction development.